PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL AUTO SERVICE CEMPAKA BARU - Savyra Dwi Putri; Rully Arifiansyah (LPPM Universitas Asa Indonesia, 2020)
This research aimed to analyze the impact of service quality which consist of reliability, responsiveness, assurance, emphaty and tangibles on customer satisfaction. The population of this research are customers of Auto Service Cempaka Baru Workshop, while samples as many as 100 respondents purposive technique. Data analyzed by multiple regression. Based on the analysis, it can be concluded that, there is a significant effect of reliability variable to the customer satisfaction with a contribution of 86,8%. There is a significant influence of responsiveness variable to customer satisfaction with contribution equal to 87,3%. There is a significant influence of assurance variable to customer satisfaction with contribution equal to 88,3%. There is a significant influence of emphaty variable to customer satisfaction with contribution equal to 80,8%. There is a significant influence of tangibles variable to customer satisfaction with contribution equal to 86,8%. If the variables are combined together it is found that there is a significant influence of the five variables to determine the customer satisfaction with a contribution of 94,2%, where other factors are influential but not discussed in this research that is equal to 5,8%